ARTERIAL HYPERTENSION AND DYSLIPIDEMIA IN PATIENTS WITH TYPE 2 DIABETES MELLITUS: RISK FACTORS, INTERVENTION STRATEGIES AND IMPACT ON CARDIOVASCULAR HEALTH. - França, Gabriel Rodrigues; Rosa, Vitor Silva; Rezende, ⁠ ⁠Eduardo Henrique Mendes; Filho, Murilo Dell Eugenio Costa; Jansen, Heldiane Estevão Maranhão; Filho, Durval José dos Santos; Pereira, Beatriz Medrado; Alves, Natana Carol; Pinotti, João Guilherme Franceschi; Araújo, Mariana Alves Anes de; Silva, João Vitor Silva da (Brazilian Journal of Implantology and Health Sciences, 2024)
Arterial Hypertension (AH) and Dyslipidemia are conditions frequently associated with Type 2 Diabetes Mellitus (DM2), significantly increasing the risk of cardiovascular disease (CVD) and mortality. The interrelationship of these metabolic risk factors becomes a growing concern due to their increasing prevalence and the serious complications they entail. AH, characterized by high blood pressure, and dyslipidemia, marked by abnormal levels of lipids in the blood, are modifiable risk factors that play central roles in the pathogenesis of cardiovascular complications of DM2. Effective intervention strategies to manage these conditions are essential to reduce cardiovascular risk in this population. Objective: To carry out a systematic review of the literature to evaluate the risk factors, intervention strategies and impact on cardiovascular health of the coexistence of AH and dyslipidemia in patients with DM2. Methodology: A search was carried out in the PubMed, Scielo and Web of Science databases for articles published in the last 10 years. The descriptors used were "arterial hypertension", "dyslipidemia", "type 2 diabetes mellitus", "cardiovascular risk factors" and "intervention". Inclusion criteria: studies that investigated the relationship between AH, dyslipidemia and DM2, therapeutic interventions for these conditions and their impact on cardiovascular health. Exclusion criteria: studies focusing exclusively on DM1, non-systematic reviews and studies with heterogeneous samples unrelated to the topic. Results: The studies reviewed highlighted the association between AH, dyslipidemia and DM2, emphasizing the importance of glycemic, lipid and blood pressure control to reduce cardiovascular risk. Multifaceted interventions, including lifestyle modifications and pharmacological therapies, have been effective in improving cardiovascular outcomes in this population. Conclusion: The integrated approach to hypertension and dyslipidemia in patients with DM2 is crucial to prevent cardiovascular complications. Personalized intervention strategies based on solid scientific evidence are critical to improving health outcomes in this high-risk population.